The paradox influence of peer groups on online gambling behavior of students at the Islamic university in Indonesia - Abrori, Ahmad; Ramadhan, Muhammad Azza; Sugianto, Aris (Center for Sociological Studies and Community Developmen, 2025)
The prevalence of online gambling among college students is increasing due to its accessibility and the significant influence of the social environment. One important element that can both encourage and discourage people from participating in this activity is peer groups. Previous research has tended to focus on only one aspect of peer group influence, and there aren't many studies that thoroughly address the multiple roles that peers play in students' online gambling decisions. Using Albert Bandura's social learning theory, this study attempts to examine how peer group social dynamics influence college students' online gambling behaviors. Using a qualitative approach, this study conducted in-depth interviews with 28 Islamic university students from different social contexts and observed their online gambling activities. The results showed that students in the peer group who gambled experienced a process of observation, retention, reproduction, and social reinforcement that increased their engagement. In contrast, students in the non-gambling peer group received negative reinforcement and social support to refrain from the behavior. These findings support the importance of peer-based prevention strategies. Therefore, campuses and stakeholders need to strengthen student communities that instill anti-gambling values and provide positive and educational alternative activities.